Creating regional guides for Scotland using encyclopaedic data: combining the Gazetteer for Scotland database and Google mapping - Taylor, Philip (My University, 2007)
Online gazetteers and encyclopaedic resources are rarely focused on a regional level, making knowledge across a spatial area difficult to acquire. This study integrated data from the Gazetteer for Scotland database (www.geo.ed.ac.uk/scotgaz) into online regional guides for Scotland, where information is organised into one web document, tied together with an interactive Google map of the region. Specific attention was paid to filtering data – both spatially and in terms of interest – and the automatic calculation of a suitable region size. An initial questionnaire and final feedback blog gathered information on the direction of the project and how well the end product achieved the above goals. The feedback blog automatically produced a Google map showing all searches performed, all of the data that users commented on and all data reported as erroneous, giving an idea of the scope of the feedback. Some interesting ideas were suggested for expansion of the project and despite several small bugs being reported, in general the methods used and results produced were praised by users of the website.
Keywords: GIS; Gazetteer for Scotland; Scotland; Travel; Google Maps; Web Service; MSc Geographical Information Science; GIS